(untitled) (Conferencea, 2023)
Pottery is a tradition for artists to refine unconventional works of art from clay and other materials. Three articles provide comprehensive information about the material of ceramics, personal, its history, techniques and current trends. The purpose of the three articles is to improve the art form and its cultural significance. Key words: ceramic art, history, technique, modern development.